Pathology of congenital Zika syndrome in Brazil: a case series. Issue 10047 (27th August 2016) - Martines, Roosecelis Brasil; Bhatnagar, Julu; de Oliveira Ramos, Ana Maria; Davi, Helaine Pompeia Freire; Iglezias, Silvia D'Andretta; Kanamura, Cristina Takami; Keating, M Kelly; Hale, Gillian; Silva-Flannery, Luciana; Muehlenbachs, Atis; Ritter, Jana; Gary, Joy; et al.
Summary: Background: Zika virus is an arthropod-borne virus that is a member of the family Flaviviridae transmitted mainly by mosquitoes of the genus Aedes . Although usually asymptomatic, infection can result in a mild and self-limiting illness characterised by fever, rash, arthralgia, and conjunctivitis. An increase in the number of children born with microcephaly was noted in 2015 in regions of Brazil with high transmission of Zika virus. More recently, evidence has been accumulating supporting a link between Zika virus and microcephaly. Here, we describe findings from three fatal cases and two spontaneous abortions associated with Zika virus infection. Methods: In this case series, formalin-fixed paraffin-embedded tissue samples from five cases, including two newborn babies with microcephaly and severe arthrogryposis who died shortly after birth, one 2-month-old baby, and two placentas from spontaneous abortions, from Brazil were submitted to the Infectious Diseases Pathology Branch at the US Centers for Disease Control and Prevention (Atlanta, GA, USA) between December, 2015, and March, 2016. Specimens were assessed by histopathological examination, immunohistochemical assays using a mouse anti-Zika virus antibody, and RT-PCR assays targeting the NS5 and envelope genes. Amplicons of RT-PCR positive cases were sequenced for characterisation of strains. Findings: Viral antigens were localised to glial cells and neurons and associated with microcalcifications in all three fatal cases with microcephaly. Antigens were also seen in chorionic villi of one of the first trimester placentas. Tissues from all five cases were positive for Zika virus RNA by RT-PCR, and sequence analyses showed highest identities with Zika virus strains isolated from Brazil during 2015. Interpretation: These findings provide strong evidence of a link between Zika virus infection and different congenital central nervous system malformations, including microcephaly as well as arthrogryposis and spontaneous abortions. Funding: None.